Intergenerational care for and by children: Examining reciprocity through focus group interviews with older adults in rural Uganda - Schatz, Enid; Seeley, Janet; Zalwango, Flavia (Demographic research, 2018)
capabilities, and on extended kin. Evidence suggests that older persons contribute extensively to children’s financial, social, psychosocial, and physical needs. Young people also provide care for older persons. Yet, most studies only capture one side of this relationship. OBJECTIVE We draw attention to intergenerational care relationship reciprocity and the likely impacts on children’s wellbeing. METHODS We analyze data from the Medical Research Council/Uganda Virus Research Institute annual population census (2015–2016) in rural Kalungu District to establish the likelihood of intergenerational care exchange at the household level. Focus group discussions (FGD) with persons aged 60-plus provide information on the types of exchanges and outcomes impacted by the presence/absence of intergenerational care. RESULTS Nearly a quarter of children (age 0–14) in our study site live in households with at least one person aged 60-plus; nearly four-fifths of persons aged 60-plus reside in a household with at least one child. The FGD data suggest that persons aged 60-plus spend considerable physical and financial resources supporting children in their networks, and simultaneously are dependent upon younger generations for various forms of support. CONCLUSIONS Older persons’ positive relationships with children in their care form a strong basis for the exchange of various types of support; when intergenerational tensions exist, reciprocal care may be less reliable. This intergenerational solidarity, or lack thereof, likely affects children’s wellbeing.
Keywords: Intergenerational care; children; reciprocity; adults; rural Uganda